M5C-Atlas: a comprehensive database for decoding and annotating the 5-methylcytosine (m5C) epitranscriptome. Issue Volume 50:Issue D1(2022) (19th November 2021) - Ma, Jiongming; Song, Bowen; Wei, Zhen; Huang, Daiyun; Zhang, Yuxin; Su, Jionglong; de Magalhães, João Pedro; Rigden, Daniel J; Meng, Jia; Chen, Kunqi
Abstract: 5-Methylcytosine (m 5 C) is one of the most prevalent covalent modifications on RNA. It is known to regulate a broad variety of RNA functions, including nuclear export, RNA stability and translation. Here, we present m 5 C-Atlas, a database for comprehensive collection and annotation of RNA 5-methylcytosine. The database contains 166 540 m 5 C sites in 13 species identified from 5 base-resolution epitranscriptome profiling technologies. Moreover, condition-specific methylation levels are quantified from 351 RNA bisulfite sequencing samples gathered from 22 different studies via an integrative pipeline. The database also presents several novel features, such as the evolutionary conservation of a m 5 C locus, its association with SNPs, and any relevance to RNA secondary structure. All m 5 C-atlas data are accessible through a user-friendly interface, in which the m 5 C epitranscriptomes can be freely explored, shared, and annotated with putative post-transcriptional mechanisms (e.g. RBP intermolecular interaction with RNA, microRNA interaction and splicing sites). Together, these resources offer unprecedented opportunities for exploring m 5 C epitranscriptomes. The m 5 C-Atlas database is freely accessible at https://www.xjtlu.edu.cn/biologicalsciences/m5c-atlas .